Density and Biomass of Seagrass Beds and Its Threats on Lamongan Regency - Dewi, Citra Satrya Utama; Yona, Defri; Samuel, Pratama Diffi; Maulidiyah, Rizqi Aimmatul; Syahrir, Ahdiya; Putri, Yandini Eka; Rakhmawan, Hilal; Fikri, Maulana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2020)
This study aims to determine the density of seagrass species, seagrass biomass, and threats faced by seagrass communities in the Coastal District of Lamongan. The study was conducted in August to November 2019 in three coastal villages of Lamongan Regency, namely Tunggul Village (Station 1), Kranji (Station 2), and Banjarwati (Station 3). The stages of the study consisted of: preparation, data collection on density, threat data and seagrass stand samples, sample processing, and data analysis. The results showed that the total density of seagrass species at Stations 1, 2 and 3 was 160 stands / m2; 172 stands / m2; and 185 stands / m2. Furthermore, the total biomass of seagrass at Stations 1, 2 and 3 was 4633 gbk / m2, 2136 gbk / m2, and 9234 gbk / m2. In addition to seagrass species, seagrass density values also affect seagrass biomass. As development progresses in Lamongan Regency, it is known that the biggest threat of seagrass communities in the study site is human activity (anthropogenic), among others: anchor ships when anchored and the use of coastal areas as tourist areas, which often cleans up seagrass communities because they are deemed unfit to be enjoyed tourism sector.